Use of the xCELLigence system for real-time analysis of changes in cellular motility and adhesion in physiological conditions - Scrace, S; O'Neill, E; Hammond, E; Pires, I (2013)
Investigation of the mechanisms behind the regulation of cellular motility and adhesion is key to understanding metastasis and the biology of tumor spreading. There are many technologies available for these studies, but the majority of them are either dependent on the use of labels or limited to endpoint analysis. The xCELLigence RTCA (real-time cell analysis) provides a platform for label free and operator independent investigation of the migration, invasion and adhesion proprieties of cells in physiologically relevant conditions. The real-time kinetic data acquisition also allows for a more accurate characterization of short-lived cellular events. In this chapter we describe the use of the xCELLigence Real-Time Cell Analyzer to investigate changes in cellular adhesion and motility in real time. © Springer Science+Business Media, LLC 2013.